The rational design of a redox-active mixed ion/electron conductor as a multi-functional binder for lithium-ion batteries. Issue 8 (1st February 2021) - Hwang, Chihyun; Lee, Jungho; Jeong, Jihong; Lee, Eunryeol; Kim, Jonghak; Kim, Seoyoung; Yang, Changduk; Song, Hyun-Kon
Abstract : A redox-active mixed ion and electron conductor (redox-active MIEC) is presented as a binder. High capacity was guaranteed, particularly at high rates due to its MIEC nature, while an additional capacity was achieved from its redox activity. Abstract : A redox-active mixed ion and electron conductor (redox-active MIEC) is presented as a binder for the lithium titanate anodes of lithium-ion batteries. The redox-active MIEC binder (symbolized by PT*-G m C n ) was designed to be (1) electrically conductive along its conjugated thiophene backbone (PT = polythiophene), (2) redox-active from its succinimide moiety (* = redox-active) and (3) ionically conductive by adopting glyme (G ) branches. It was superior to the practically used PVdF binder in terms of lithium ion diffusivity and electrical conductivity (1.4× and 15 000×, respectively). High capacity was guaranteed, particularly at high rates due to its MIEC nature of PT*-G m C n, while an additional capacity was achieved from its redox activity.